2018 IEEE International Symposium on Information Theory (ISIT) 2018
DOI: 10.1109/isit.2018.8437587
|View full text |Cite
|
Sign up to set email alerts
|

Multilevel-Coded Pulse-Position Modulation for Covert Communications

Abstract: We develop a low-complexity coding scheme to achieve covert communications over binary-input discrete memoryless channels (BI-DMCs). We circumvent the impossibility of covert communication with linear codes by introducing non-linearity through the use of pulse position modulation (PPM) and multilevel coding (MLC). We show that the MLC-PPM scheme exhibits many appealing properties; in particular, the channel at a given index level remains stationary as the number of level increases, which allows one to use fami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…All our achievability results are established using Pulse-Position Modulation (PPM), which optimality was previously only established for the first-order asymptotics with relative entropy [16]. The operational relevance of codes used in conjunction with PPM, which may be viewed as a highly structured subset of constant composition codes, is justified by recent work towards practical code design [17], in which PPM plays a crucial role. We also emphasize from the outset that the focus on maximal probability of error is essential to our analysis.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…All our achievability results are established using Pulse-Position Modulation (PPM), which optimality was previously only established for the first-order asymptotics with relative entropy [16]. The operational relevance of codes used in conjunction with PPM, which may be viewed as a highly structured subset of constant composition codes, is justified by recent work towards practical code design [17], in which PPM plays a crucial role. We also emphasize from the outset that the focus on maximal probability of error is essential to our analysis.…”
Section: Introductionmentioning
confidence: 95%
“…towards practical code design [17], in which PPM plays a crucial role. We also emphasize from the outset that the focus on maximal probability of error is essential to our analysis.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that in many relevant scenarios when the Warden channel is worse than the Alice-Bob channel the maximum number of bits that can be reliably transmitted while keeping the transmission covert from the Warden grows asymptotically as O( √ n), being n the codeword length, even if Alice and Bob do not share any secret key. Furthermore, a scheme based on pulse position modulation (PPM) that is asymptotically optimal has been proposed for binary-input discrete memoryless channels and the Gaussian channel ( [5], [6], [7]). In all these works the focus has been on the amount of information bits that could be sent when the codeword length increased unbounded.…”
Section: Introductionmentioning
confidence: 99%
“…The chips in symbols (0) and (3) flip and recombine, resulting in a two-symbol substitution (03) → (21). The chip in symbol (0) flips from '1' to '0', and these '0' chips merge with the successive symbol (2), resulting in a deletion, i.e., (02) → (3). Therefore, the DPPM modulation, the AWGN channel and the DPPM detection can be considered as a general insertion/deletion/substitution (IDS) channel [28].…”
Section: Introductionmentioning
confidence: 99%